Scilab based toolbox for fractional-order systems and PID controllers - Bingi, K. (Springer International Publishing, 2020)
In this chapter, a toolbox for fractional-order systems and PI/PID controllers using Scilab will be developed. According to our knowledge, the proposed toolbox is the first Scilab based toolbox for fractional-order systems and controllers. The toolbox will be developed in three stages. Initially, the definitions of fractional-order operators, approximation algorithms and fractional-order differentiator and integrator will be implemented. Using these definitions in the second stage, fractional-order systems, controllers, and filters will be developed. The final stage includes the time and frequency domain analysis as well as numerical and stability analysis of the systems. Â© Springer Nature Switzerland AG 2020.